Improvement of mechanical heart function by trimetazidine in db/db mice - Li Yuan-jing; Wang Pei-hua; Chen Chen; Zou Ming-hui; Wang Dao-wen (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the influence of trimetazidine, which is known to be an antioxidant and modulator of metabolism, on cardiac function and the development of diabetic cardiomyopathy in db/db mouse. Methods: Trimetazidine was administered to db/db mice for eight weeks. Cardiac function was measured by inserting a Millar catheter into the left ventricle, and oxidative stress and AMP-activated protein kinase (AMPK) activity in the myocardium were evaluated. Results: Untreated db/db mice exhibited a significant decrease in cardiac function compared to normal C57 mice. Oxidative stress and lipid deposition were markedly increased in the myocardium, concomitant with inactivation of AMPK and increased expression of peroxisome proliferator-activated receptor coactivator-1α (PGC-1α). Trimetazidine significantly improved systolic and diastolic function in hearts of db/db mice and led to reduced production of reactive oxygen species and deposition of fatty acid in cardiomyocytes. Trimetazidine also caused AMPK activation and reduced PGC-1α expression in the hearts of db/db mice. Conclusion: The data suggest that trimetazidine significantly improves cardiac function in db/db mice by attenuating lipotoxicity and improving the oxidation status of the heart. Activation of AMPK and decreased expression of PGC-1α were involved in this process. Furthermore, our study suggests that trimetazidine suppresses the development of diabetic cardiomyopathy, which warrants further clinical investigation.